1974
DOI: 10.1037/h0036017
|View full text |Cite
|
Sign up to set email alerts
|

Developmental study of balance, agreement, and attraction effects in the ratings of hypothetical social situations.

Abstract: A study was conducted in which children in four age groups-5-6, 7-8, 9-10, and 11-12 years-rated eight hypothetical social situations of the P-O-X type for pleasantness and for psychological consistency. The results indicated that children in all age groups based their ratings of both pleasantness and consistency primarily on attraction (i.e., the sign of the P/O bond). Balance and agreement effects, although statistically significant, were small in all groups. The findings were confirmed in a cross-validation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

1979
1979
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…The contact interpretation cannot account for such a difference, and it is clear that any totally adequate interpretation of the attraction and agreement effects must be able to explain their differential magnitudes. Second, consistent with indications from earlier studies (Crockett, 1974;Gutman and Knox, 1972;Gutman, Knox and Storm, 1974;Miller and Norman, 1976) that pleasantness scales reveal larger attraction and agreement effects than do consistency and/or expectancy scales, Insko and Adewole (1979) found in two separate studies that ratings on affective scales (pleasantness and harmony) yield larger attraction and agreement effects than do ratings on relatively more cognitive scales (expectancy, consistency and stability). Again, there is no obvious way in which the contact interpretation of the attraction and agreement effects can account for such results.…”
Section: Introductionsupporting
confidence: 80%
“…The contact interpretation cannot account for such a difference, and it is clear that any totally adequate interpretation of the attraction and agreement effects must be able to explain their differential magnitudes. Second, consistent with indications from earlier studies (Crockett, 1974;Gutman and Knox, 1972;Gutman, Knox and Storm, 1974;Miller and Norman, 1976) that pleasantness scales reveal larger attraction and agreement effects than do consistency and/or expectancy scales, Insko and Adewole (1979) found in two separate studies that ratings on affective scales (pleasantness and harmony) yield larger attraction and agreement effects than do ratings on relatively more cognitive scales (expectancy, consistency and stability). Again, there is no obvious way in which the contact interpretation of the attraction and agreement effects can account for such results.…”
Section: Introductionsupporting
confidence: 80%
“…People generally like those with whom they agree, in part because having one's view of the world validated is reinforcing (e.g., Byrne, 1961;Clore & Baldridge, 1968;Condon & Crano, 1988;Festinger, 1951;Gutman, Knox, & Storm, 1974;C. E. Miller & Norman, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…This may be a particularly difficult set of issues to untangle, as research has repeatedly shown that similarity and likability are strongly related (e.g., Bornstein, 1989;Byrne, 1961;Byrne et al, 1966;Byrne et al, 1967;Clore & Baldridge, 1968;Condon & Crano, 1988;Gutman et al, 1974;C. E. Miller & Norman, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…One of these factors relates to the type of rating scale. Existing research by Crockett (1974); Gutman and Knox (1972); Gutman, Knox, and Storm (1974);and Miller and Norman (1976) suggests that pleasantness scales reveal larger attraction effects than do consistency and/or expectancy ratings. Experiment 1 contains a scales factor that includes five different rating scales: pleasant-ness, harmony, expectancy, consistency, and stability.…”
mentioning
confidence: 96%